Dilute Sulfuric Acid Hydrolysis Of Red Macroalga Eucheuma Denticulatum With Microwaveassisted Heating For Biochar And Bioethanol Production - Teh, Yong Yi (2018)
Eucheuma denticulatum is a type of red macroalgae which are considered as potential feedstock for biofuel production due to high carbohydrate content, ease of availability and low arable land usage. Being such abundant in carbohydrates, macroalgae can be hydrolysed into fermentable sugars and converted to bioethanol by natural microorganims. However, the conventional thermal heating that delivers heat from the surface to center of a material is comparatively slow and inefficient. As a result, the longer heating time gives rise to a dramatic reduction of reducing sugars but higher content of by-products, consequently inhibiting the subsequent fermentation. In this study, acid hydrolysis with microwave-assisted heating of macroalga was conducted in a 2.45 GHz microwave oven with 800W of power. The rapid and efficient of dielectric heating effect of microwave-assisted heating could address aforementioned problem, enhance the hydrolysis process and co-produce biochar, reducing sugars and valuable chemicals. This study was set out to study the properties of biochar as a source of biofuel after macroalga was subjected to microwave-assisted hydrolysis. The hydrolysis reactions were operated at sulfuric acid concentrations of 0.1M and 0.2M, reaction temperatures of 150–170 °C and a heating time of 10 min. The produced biochars were characterized and it was found that biochar qualities were improved with increased elemental carbon content and lower ash and moisture contents. The calorific value of the biochar was intensified up to 45%, and 39% of energy yield was recovered. Apart from biochar, the concentrations of reducing sugars and by-product of hydrolysate were also determined and subsequently converted to bioethanol. The highest total reducing sugars were 51.47 g/L (74.84% yield) along with a low by-product 5-HMF of 0.20 g/L, when the biomass was treated under the conditions at 160 °C with 0.1M H2SO4. The ethanol yield obtained was 0.33 g/g, which corresponded to a 64.21% of yield. As a conclusion, acid hydrolysis with microwave-assisted acid hydrolysis has its great potential applications for the production of bioenergy, nutrient-rich biochar for soil amelioration and value-added chemicals.